Does dysfunction of the autonomic nervous system affect success of renal denervation in reducing blood pressure?. (3rd April 2017) - Fricke, Lisa; Petroff, David; Desch, Steffen; Lurz, Philipp; Reinhardt, Sebastian; Sonnabend, Melanie; Classen, Joseph; Baum, Petra
Objectives: Renal denervation is an interventional approach aiming to reduce high blood pressure. Its efficacy is subject of controversial debate. We analyzed autonomic function in patients undergoing renal denervation to identify responders. Methods: A total of 21 patients with treatment-resistant hypertension scheduled for renal denervation were included. Heart rate variability, pupillary function and sympathetic skin response were examined prior to intervention. Before and 1 or 3 months after intervention, 24-h ambulatory blood pressure readings were taken. Results: Patients were stratified according to sympathetic nervous system function. Sympathetic activity was reduced in 12 participants (group 1) and normal or enhanced in nine patients (group 2). The mean of daytime systolic blood pressure decreased in groups 1 and 2 from 168 to 157 mmHg (95% confidence interval for difference, 1–21 mmHg, p = 0.035) and from 166 to 145 mmHg (8–34 mmHg, p = 0.005), respectively. In a linear model, blood pressure reduction was 11.3 mmHg (0.3–22 mmHg) greater in group 2 than in group 1 (p = 0.045). Conclusion: Patients with preexisting reduced activity of the sympathetic nervous system benefited less from renal denervation.